[12]aneN3-based multifunctional compounds as fluorescent probes and nucleic acids delivering agents. (1st January 2020) - Gao, Yong-Guang; Huangfu, Shu-Yuan; Patil, Suryaji; Tang, Quan; Sun, Wan; Li, Yu; Lu, Zhong-Lin; Qian, Airong
Abstract: A series of multifunctional compounds (MFCs) 1a –1e based on 1, 8-naphthalimide and [12]aneN3 building blocks were designed and synthesized. They were used as not only fluorescent probes for recognition of Cu 2+ ions but also as non-viral gene vectors for DNA and RNA delivery. Furthermore, their complexes with Cu 2+ (1 -Cu) could also selectively stain lysosome in HeLa cells. In order to achieve high performance multifunctional materials, structure-performance relationship of MFCs 1a–1e was studied. It was found that MFCs 1a –1e exhibited highly selective fluorescence turn-off for Cu 2+, without interference by other metal ions in aqueous solution. The fluorescence emission of 1a–1e was quenched by a factor of 10-fold, 47-fold, 6-fold, 64-fold, and 15-fold respectively in the presence of Cu 2+ ions. Due to high sensitivity, good water solubility, and low cytotoxicity, MFCs 1a–1d were successfully applied in the recognition of Cu 2+ and selectively staining lysosome in HeLa cells. Most importantly, MFCs 1a and 1b had excellent HeLa cell selectivity in RNA delivery, and their performances were far better than lipofectamine 2000 and 25 kDa PEI.